Affective Norms for 718 Polish Short Texts (ANPST): Dataset with Affective Ratings for Valence, Arousal, Dominance, Origin, Subjective Significance and Source Dimensions - Imbir, Kamil K. (Frontiers in Psychology, 2016)
Affective sciences are of burgeoning interest and are attracting more and more research attention. Three components of stimuli meaning have traditionally been distinguished: valence (degree of pleasantness), arousal (degree of intensity of sensations), and dominance (degree of control over sensations). Recently, another three dimensions have been introduced to measure qualities connected to the emotion–duality model: origin (the main component originating in the heart or in the mind), subjective significance (the degree of the subjective goal’s relevance), and source (the location of the stimuli evoking the state). All six affective dimensions were assessed in our study of 718 Polish short texts (sentences of 5–23 words and 36–133 characters in length) describing situations or states in a way that can be referenced to an individual’s experience. Assessments were carried out by 148 psychology students (all women for 108 sentences) and 2,091 students of different faculties (social science, engineering, life science, and science) from Warsaw colleges and universities (1,061 women and 1,030 men for all 718 sentences). Assessing sets of sentences for emotional response is especially useful for researchers interested in emotion elicitation through the use of a phrase such as “imagine that …” or by simply reading emotionally charged material that is more complex and that provides better context than single pictures or words.